Deciphering the prognostic impact of aberrant DNA methylation on ANGPT1 gene in breast cancer - Mansour Alsaleem; Samar Sindi; Safiah Alhazmi; Sabah Hassan; Magdah Ganash; Najla Alburae; Shadi Alkhayyat; Ayman Linjawi; Aisha Elaimi; Saif A. Alharthy; Khloud Algothmi; Reem Farsi; et al. (Scientific Reports)
Abstract Breast cancer (BC) is a multifaceted disease distinguished by a range of molecular subtypes and varying clinical prognoses. The involvement of DNA methylation in the dysregulation of gene expression has been linked to the development and progression of BC. Therefore, this study aimed to investigate the association between ANGPT1 gene expression and DNA methylation in BC patients. Eight Saudi female blood samples were used to undergo for whole genome bisulfite sequencing (WGBS) and RNA sequencing for the identification of novel DNA methylation targets. Several public domain BC datasets including the METABRIC cohort, TCGA, and Kaplan Meier Plotter datasets, were used to explore the prognostic significance of ANGPT1 gene. Then, the demethylation agent 5-aza-2’-deoxycytidine was used to examine the potential association between DNA methylation and ANGPT1 expression. Finally, the validation was conducted on blood samples from 49 Saudi females using methylight techniques. Our results shows that upregulation of ANGPT1 gene expression exhibited hypomethylation pattern in BC samples. these results were confirmed by MCF7 cell line experiments. Demethylating using 5-aza in MCF7 and MCF10A showed a high expression of ANGPT1 in both cell lines. ANGPT1 mRNA expression was found to poor prognostic biomarker and lower Breast Cancer-Specific Survival (BCSS) in BC patients. The potential importance of abnormal DNA methylation in the development and advancement of BC is significant. ANGPT1 may act as an oncogene and could be extensively studied further to behave as a predictive biomarker for breast cancer.